Autómatas Celulares en Cascada para modelar la expansión urbana con áreas restringidas - Jiménez López, Eduardo; Garrocho Rangel, Carlos; Chávez Soto, Tania (El Colegio de México A.C., 2021)
We combine urban geography, dynamic system mathematics, geographic information systems (GIS) and computer science to design a general modeling methodology based on Cascade Cellular Automata, which allows the construction of specific models of the expansion of Mexican cities. We submit our methodology to a triple empirical test in contrasting cities. The models consider restrictions on urban expansion (e.g., roads, parks, coasts). We use global and local indicators of goodness of fit between images articulated in a cascade filter, which reduces computational processing. The models showed encouraging adjustments. We illustrate how our method can drive the co-design of urban policies.